Fractional Control of Dynamic Systems - Barbosa, Ramiro S. (2011)
The concepts involved with fractional calculus (FC) theory are applied in almost all areas of science and engineering. Its ability to yield superior modeling and control in many dynamical systems is well recognized. In this article, we will introduce the fundamental aspects associated with the application os FC to the control of dynamic systems.